Dynamic changes in Id3 and E-protein activity orchestrate germinal center and plasma cell development - Gloury, Renee (J Exp Med, 2016)
The generation of high-affinity antibodies requires germinal center (GC) development and differentiation of long-lived plasma cells in a multilayered process that is tightly controlled by the activity of multiple transcription factors. Here, we reveal a new layer of complexity by demonstrating that dynamic changes in Id3 and E-protein activity govern both GC and plasma cell differentiation. We show that down-regulation of Id3 in B cells is essential for releasing E2A and E2-2, which in a redundant manner are required for antigen-induced B cell differentiation. We demonstrate that this pathway controls the expression of multiple key factors, including Blimp1, Xbp1, and CXCR4, and is therefore critical for establishing the transcriptional network that controls GC B cell and plasma cell differentiation.